Association of the feeling of anxiety and the phenomenon of inferiority - O.R. Berezyuk; O.O. Filts (Medičnì Perspektivi)
The phenomenon of inferiority as a key concept of Adler's theory of psychology can contribute to the appearance of social anxiety. Since both anxiety and feeling of inferiority have an impact on mental and somatic health, the aim of the study was to investigate the association of the phenomenon of inferiority with the feeling of anxiety. During October-November 2021 in the course of the study, a questionnaire survey of 612 students of higher education institutions of Lviv was conducted. Two questionnaires were used for the survey: the Comparative Feeling of Inferiority Index and Beck's Anxiety Inventory. The analysis of the findings was performed using the methods of descriptive (median, 25% and 75% quartiles, percentages with 95% confidence intervals) and analytical statistics (Kruskal-Wallis test, Dunn's post-hoc paired test, Pearson's test). The research established that the feeling of anxiety is characteristic of 54.95% [45.67-64.07] of the respondents with the Index of Superiority, 48.84% [34.17-63.61] of the respondents with the Index of Inferiority and 43.91% [39.60-48.28] of respondents with the absence of the phenomenon of altered self-esteem (Norma). Median scores on Beck's Anxiety Inventory were significantly higher in individuals with the index of superiority – 8.5 [5; 16.3] points. A comparison of the presence of anxiety by gender showed that anxiety symptoms are significantly more common in women than in men: 57.85% [51.82-63.77] vs 37.04% [32.07-42.15] respectively, p<0.001. Anxiety is most often characteristic of women with the index of superiority – 76.67% [60.16-89.79]) of women in this group. The value of the findings is determined by the fact that in Ukraine this is the first scientific study regarding the research of the association of the phenomenon of inferiority and anxiety in adult population with using proven and valid questionnaires that are actively used by scientists around the world.